The Off-Design Modelling of a Combined-Cycle Power Plant - Naidu, Rushavya (Department of Mechanical Engineering, 2021)
The shift towards renewable energy has steered the focus of power plant operation towards flexibility and fast response which are more attainable through the use of combined-cycle power plants. These aspects are required to account for the fluctuation of the supply as well as the demand of power that is associated with renewable energy. Combined-cycle power plants consist of a gas turbine as the topping cycle, forming the core of the plant, and a Rankine cycle with a steam turbine as the bottoming cycle. A component called the Heat Recovery Steam Generator (HRSG) forms a connection point between the two cycles. It uses the heat released from the gas turbine to produce high pressure and temperature steam to be sent to the steam turbine. The objective of this project is to develop a model of a combined-cycle power plant in Flownex which can be solved in off-design conditions in order to compare it to plant data. The verification of this model will show that Flownex can be used to effectively and efficiently model a combined-cycle power plant. The process of development of the final Flownex model was achieved using various additional software. Initially, an analytical model was developed in Mathcad (software used for engineering calculations). This software provides a tool for understanding knowns, unknowns and what is being calculated in the system. Manual calculations of the Heat Recovery Steam Generator (HRSG) were done using heat balance equations. A temperature profile of the gas and water/steam in the HRSG was developed so that the duties of each component (economiser, evaporator, superheater) could be calculated. The overall conductance (UA) of each component was calculated in the design mode for the system to be evaluated in off-design mode. The development of an analytical model provided detailed understanding of the process of mathematical modelling used in commercial tools. Thereafter, a model was built in Virtual Plant, a thermodynamic modelling software for assessing plant performance. Virtual Plant uses plant design information and first engineering principles to predict plant performance. Finally, the Flownex model was designed. Flownex uses endpoint values (initial pressure and temperature and outgoing mass flow) and the UA of each component to calculate the characteristics of the flow at each intermediate point. For the single-, double-, and triple-pressure combined-cycle power plant systems, the analytical, Virtual Plant and Flownex models were compared. The results of all the models agreed closely with one another. The triple-pressure design and off-design Virtual Plant and Flownex models were also compared to plant data and it was concluded that Flownex was successful in modelling the design and off-design conditions of a combined-cycle power plant.